The psychology of terrorism fears - Sinclair, Samuel J., 1975-; Antonius, Daniel (New York ; Oxford : Oxford University Press, 2012)
The psychology of terrorism, in its most basic form, is about fear. The purposes of this book are to unpack the complexity of terrorism fears and to present a new paradigm for understanding the psychology of terrorism.
Includes bibliographical references.
Description based on online resource; title from PDF title page (viewed on May 15, 2012).
Keywords: Terrorism -- Psychological aspects; Terrorism -- Prevention